Satellite Image Map West-Neuschwabenland 1:3 000 000 1982, Antarktis - Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie); Frankfurt am Main (Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie), Frankfurt am Main, 1982)
Satellite image mosaic, NOAA-6 and 7-AVHRR, Records taken from Dec 1981 to March 1982, Geometrically rectified using 19 ground control points, 500m-contours on the mainland taken from GEBCO Chart 5.18 at 1.6 000 000 scale, 1980; Map graticule, Inset maps: Location diagram, Imagery coverage diagram Scale: 1:3000000; Projection: Polar Stereographic; Bounding Box: POLYGON ((-15 -68.5, 25 -68.5, 30 -72.5, 11 -74.5, 11 -76, -20 -76, -15 -68.5))